Gelatin Encapsulated Curcumin Nanoparticles Moderate Behavior of Human Primary Gingival Fibroblasts In Vitro. (9th July 2020) - Nguyen, Mai Thi-Hoang; Ly, Khanh Loan; Kieu, Thoai Quoc; Nguyen, Hiep Thi; Huynh, Nam Cong-Nhat
Abstract : Objective. Currently, there is no study evaluating the effect of nano-curcumin on human oral cells in vitro. In this study, we developed gelatin encapsulated curcumin nanoparticles (GelCur) and cultured the primary human gingival fibroblasts (hGFs) to verify the effect of GelCur on the cellular events related to oral wound healing capacities, such as cell migration and proliferation of gingival fibroblasts. Materials and Methods. GelCur was produced by the sonoprecipitation method. Particle size, zeta potential, SEM morphological observation, entrapment efficiency, and drug loading were used to characterize new GelCur. Primary hGFs were cultured from the attached gingival tissue of healthy third molar teeth. The effect of different concentrations of GelCur on hGFs was investigated by cell toxicity assay (MTT), cell proliferation assay, and cell migration assays by scratch test and transwell migration assay. Results. The average particle size of GelCur was around 356 nm with a moderate zeta potential of 26.5 mV. The mean PdI value of GelCur was 0.2, while the entrapment efficiency and drug loading of curcumin in this study were around 57% and 2.4%, respectively. IC30 of GelCur on hGFs was 3.96 mg/ml, while IC50 was 12, 37 mg/ml. More than 70% of cells were viable after 24 hours incubated with 1, 2, and 3 mg/ml GelCur. At the concentration of 2 mg/ml GelCur virtually limited cell proliferation and migration. Conclusions. GelCur remained physically stable and did not alter cell proliferation and migration. The concentration of GelCur <3.96 mg/ml did not cause hGF cytotoxicity. Our study showed that within appropriate doses, GelCur can be used safely for hGFs.